2015
DOI: 10.1111/nph.13629
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene biosynthesis potential of plant subcellular compartments

Abstract: SummarySubcellular monoterpene biosynthesis capacity based on local geranyl diphosphate (GDP) availability or locally boosted GDP production was determined for plastids, cytosol and mitochondria.A geraniol synthase (GES) was targeted to plastids, cytosol, or mitochondria. Transient expression in Nicotiana benthamiana indicated local GDP availability for each compartment but resulted in different product levels. A GDP synthase from Picea abies (PaGDPS1) was shown to boost GDP production. PaGDPS1 was also target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 53 publications
8
82
0
Order By: Relevance
“…A possible downside of the approach can be the ability of endogenous tobacco enzymes to further modify the enzymatic products. For example, it is established that tobacco often glycosylates products of heterologous enzymes resulting in a multitude of glycoside products [61]. This can be circumvented by the use of glycosylase formulations, such as Viscozyme (Sigma-Aldrich) to deglycosylate the compounds to their original form prior to analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible downside of the approach can be the ability of endogenous tobacco enzymes to further modify the enzymatic products. For example, it is established that tobacco often glycosylates products of heterologous enzymes resulting in a multitude of glycoside products [61]. This can be circumvented by the use of glycosylase formulations, such as Viscozyme (Sigma-Aldrich) to deglycosylate the compounds to their original form prior to analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that numerous endogenous Nicotiana metabolites are decorated with sugars (Kodama et al, 1984;Pang et al, 2007;Jassbi et al, 2010;Heiling et al, 2016;Yuan et al, 2018) and newly formed metabolites are subjected to glycosylation (Dong et al, 2013(Dong et al, , 2016. The glycosylation reactions are catalyzed by uridine diphosphate dependent glycosyltransferases (UGT) that transfer carbohydrates from nucleotide-sugar donors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Catharanthus roseus, accumulation of secologanin, a geraniol derived-monoterpene indole alkaloid, was achieved upon overexpression of CrGES along with a bifunctional CrG(G)PPS [259,260]. In addition, a combinatorial production of geraniol in tobacco has been examined using different subcellular compartments (i.e., plastids, cytosol or mitochondria): results showed that plastid-targeted VoGES combined with expression GPPS from Picea abies (PaGDPS1) for GPP overproduction lead to the highest production of geraniol [261].…”
Section: Geraniol (C 10 H 18 O Monoterpenoid)mentioning
confidence: 99%